Experiences of women undergoing abdominoplasty in the public sector: a qualitative study - Nicola R Dean; Kristen Foley; Randall Long; Paul Ward (Australasian Journal of Plastic Surgery)
**Introduction** This study was designed to improve understanding of the experiences of women undergoing abdominoplasty in a public hospital setting, including their experience of processes of care, surgical treatment and outcomes of surgery.